Organizational learning: Prospective on employees readiness using information system supported learning - Turi, Jamshid Ali; Sorooshian, Shahryar; Ghani, Muhammad Faizal A.; Javed, Yasir; Ali, Asif (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2018)
This study examined the theoretical, historical, philosophical prospective, perceptions and readiness of employees for information system supported learning in a learning organization. In this study, a conceptual model based on the theory of planned behaviour is used which explains how employees in learning organization conceive organizational learning using information systems. Structural Equation Mdelling (SEM) was used to analyse data from 200 employees including knowledge employees, faculty members, postgraduate working employees (internees), administrators and internees at university using convenient sampling techniques. The results show that employees’ acceptance of an Information System for organizational learning is reasonably well, based on the theory of planned behaviour. More specifically, attitude and behavioural control positively influenced their intention to accept organizational learning through an information system. The research shows that perceived ease of use and perceived usefulness affects employees’ and working employees’ attitude towards adoption of an information system for organizational learning.